Glucagon-Like Peptide-1 Agonist Exendin-4 Facilitates the Extinction of Cocaine-Induced Condition Place Preference - Zhu, Changliang; Hong, Tao; Li, Hailiang; Jiang, Shucai; Guo, Baorui; Wang, Lei; Ding, Jiangwei; Gao, Caibin; Sun, Yu; Sun, Tao; Wang, Feng; Wang, Yangyang; et al. (Frontiers in Systems Neuroscience, 2021)
Accumulating studies suggest that the glucagon-like peptide-1 receptor agonist exendin-4 (Ex4) and toll-like receptor 4 (TLR4) play a pivotal role in maladaptive behavior of cocaine. However, few studies have assessed whether Ex4 can facilitate the extinction of drug-associated behavior and attenuate the reinstatement of cocaine-induced condition place preference (CPP) in mice. The main objective of the present study was to evaluate Ex4’s ability to regulate the extinction and reinstatement of cocaine-induced CPP. C57BL/6 mice were conditioned to either cocaine (20 mg/kg) or an equivalent volume of saline to establish a cocaine-mediated CPP paradigm. To investigate the potential effects of Ex4 on extinction, animals received an intraperitoneal injection of Ex4 either immediately or 6 h after each extinction or only on the test day. The persistence of extinction was measured using the reinstatement paradigm evoked by 10 mg/kg of cocaine. To explore the possible impacts of Ex4 and neuroinflammation on cocaine, the expression levels of TLR4 within the hippocampus was detected using western blotting. As a result, we found that systemic administration of Ex4 immediately after each extinction training, instead of 6 h after each extinction and on the day of extinction test, was capable of facilitating extinction in the confined or non-confined CPP extinction paradigms and blocking the cocaine-primed reinstatement of cocaine-induced CPP. Additionally, we also observed that Ex4 was competent to alleviate TLR4 signaling that has been up-regulated by cocaine. Altogether, our findings indicated that the combination of Ex4 with daily extinction training was sufficient to facilitate extinction of the conditioned behavior, attenuate reinstatement of cocaine-induced CPP and inhibit TLR4 signaling. Thus, Ex4 deserves further investigation as a potential intervention for the treatment of cocaine use disorder